Efektivitas Program Bantuan Sosial Tunai Kepada Masyarakat Terdampak Pandemi Covid-19 Di Kelurahan Timbang Galung Kecamatan Siantar Barat Kota Pematangsiantar - Dwi Adriani Sumantri; Asima Yanty Sylvania Siahaan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
After the stipulation of COVID-19 as a national disaster, the government through the Ministry of Social Affairs launched the BST program for communities affected by the COVID-19 outbreak. This study aims to describe in depth the effectiveness of the Cash Social Assistance Program for Communities Affected by the COVID-19 Pandemic in Timbang Galung Village, Siantar Barat District, Pematangsiantar City. The method used in this research is descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observation, and documentation. The results showed that the Effectiveness of the Cash Social Assistance Program to Communities Affected by the COVID-19 Pandemic in Timbang Galung Village, West Siantar District, Pematangsiantar City, has not been effective. This can be seen from the data collection carried out that still does not meet the accuracy of the program due to the lack of accuracy of program managers in the process of collecting data on program participants. In addition, the socialization between program managers and the community did not go well because there was no socialization implementation. Thus, the linkage of these elements results in inaccuracy of program targets, lack of performance of program managers, and not achieving program objectives.